Kualitas Pelayanan Publik Berbasis Aplikasi E-Lapor (Dinas Komunikasi dan Informatika Pemerintah Provinsi Jawa Timur) - Rena Eprilly Widodo; Supri Hartono; Endang Indartuti (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Technology that has developed today can be a source of information from all media using internet networks easily favored by the community. The information obtained is faster, more accurate and can be used wherever technology arises, some problems are encountered by the community so that a program or policy is needed that can solve the problems they face. The solution can be from the community itself or the government that supports to improve the quality of public services, there needs to be increased efficiency and transparency. The purpose of this study is to measure how the quality of the implementation of the E-Report application in East Java with the improvement of public services implemented by the East Java Provincial Communication and Information Office. In this study using qualitative research type descriptive method and the type of data collection used is by conducting interviews, direct observation, and documentation. Measurement indicators use Zeithahaml and Parasuraman &; Berry theory which are indicators of tangibility, reliability, responsiveness, assurance and empathy. The result is that there are still indicators that have not met and make it less run optimally, obstacles such as lack of human resources, this complaint application still has weaknesses that make the community still unfamiliar due to lack of socialization between districts and sub-districts, lack of response and follow-up of complaints that make complaints slow by regional officials.